Pengaruh Risiko Kredit, Dana Pihak Ketiga dan Pendapatan Bunga Terhadap Penyaluran Kredit Perbankan - Sifa Nurbaiti; Anggun Anggraini (CV. ITTC INDONESIA, 2024)
This research aims to determine the influence of the credit risk, third party funds and interest income on bank credit distribution. The type of research used is a quantitative approach with associative methods. The sampling technique in this research is purposive sampling. The population of this research is 46 companies in the conventional commercial banks and sharia commercial banks listed on the Indonesia Stock Exchange and after following the sampling criteria, there were 28 companies with a research period of 5 (five) years resulting in 140 observation data. The data analysis technique used is panel data regression using E-views 12 software. The F test results show that the credit risk, third party funds and interest income simultaneously influence bank credit distribution. The t test results show that the credit risk has no effect on bank credit distribution, while third party funds has a positive effect on bank credit distribution and interest income has a positive effect on bank credit distribution.